Common animals: sedentary pastoralism and the emergence of the commons as an institution - Kanne, Katherine; Haughton, Mark; Lash, Ryan (Frontiers in Human Dynamics, 2024)
Animal husbandry was of fundamental consequence in the planning and development of larger and more permanent communities. Pastoralism is often assumed to be highly mobile when considering social institutions and political formations, despite the diversity of husbandry practices that are either wholly, or largely, tethered to relatively sedentary social aggregations. Key tenets of more settled animal husbandry are intensive social relations between people, and between people, animals, and landscapes. This entails reciprocal, multispecies cooperative efforts to decide how to utilize pastoral resources, choose where to settle, and how to organize settlements with an eye for the animals. Yet, scholars have rarely considered how the logistics and social dynamics of pastoralism shaped the transition to sedentism and, particularly, the development of collective forms of governance in prehistory. In this paper, we re-center pastoralism in narratives of settling down, in order to recognize the critical ways that relations with animals shaped how humans learned to move and dwell in emergent grazing landscapes. We take an institutional approach to the concept of “the commons,” demonstrating the dynamics through 19th-century Irish rundale, then draw on case studies from Southern Scandinavia and the Carpathian Basin to consider the commons as a multispecies institution which resulted in variable sociopolitical formations of the European Bronze Age.